Diana, princess of the Amazons - Hale, Shannon; Hale, Dean, 1972- (DC Comics, 2020)
Eleven-year-old Diana, the gangly, sometimes clumsy, only child on the island of Themyscira, struggles to live up to the high Amazonian standards and longs for someone her own age whom she can talk to.